The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1128/iai.01359-12
|View full text |Cite
|
Sign up to set email alerts
|

The Early Dissemination Defect Attributed to Disruption of Decorin-Binding Proteins Is Abolished in Chronic Murine Lyme Borreliosis

Abstract: The laboratory mouse model of Lyme disease has revealed that Borrelia burgdorferi differentially expresses numerous outer surface proteins that influence different stages of infection (tick-borne transmission, tissue colonization, dissemination, persistence, and tick acquisition). Deletion of two such outer surface proteins, decorin-binding proteins A and B (DbpA/B), has been documented to decrease infectivity, impede early dissemination, and, possibly, prevent persistence. In this study, DbpA/B-deficient spir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
42
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 54 publications
(84 reference statements)
2
42
1
Order By: Relevance
“…Here again, immune evasion could be key; the revA-deficient mutant may be inducing a more pronounced, but tissue-specific, inflammatory response that causes damage to the host while failing to clear the bacteria. Studies of the establishment and early dissemination of bacteria deficient in other adhesins, such as DbpA and BBK32, have hinted at roles in avoiding immune clearance (24,68). Further research employing bioluminescent whole-body imaging, combined with comprehensive examination of tissuespecific pathology and immune responses, could provide insights into the role of RevA in both dissemination and colonization in the early stages of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Here again, immune evasion could be key; the revA-deficient mutant may be inducing a more pronounced, but tissue-specific, inflammatory response that causes damage to the host while failing to clear the bacteria. Studies of the establishment and early dissemination of bacteria deficient in other adhesins, such as DbpA and BBK32, have hinted at roles in avoiding immune clearance (24,68). Further research employing bioluminescent whole-body imaging, combined with comprehensive examination of tissuespecific pathology and immune responses, could provide insights into the role of RevA in both dissemination and colonization in the early stages of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Tissues contain diversity within their ECM, with various subunits and ratios of collagens, fibronectin, integrins, fibrinogen, and laminin (65). ECM-binding adhesins have been characterized in many pathogens, and some have been discovered in B. burgdorferi, including DbpA, BBK32, P66, Bgp, BBB07, and BBA33 (21)(22)(23)(24)(25)(26)(27)54). B. burgdorferi has an outer surface rich in lipoproteins, many of which are hypothesized to interact with host structures and provide for optimal adhesion and/or immune evasion.…”
Section: Discussionmentioning
confidence: 99%
“…B. burgdorferi may travel through the lymphatic system not only for dissemination but also to interfere with the im-mune response and gain a survival advantage for spirochetes infecting all tissues (39). Recent studies have also found that, in contrast to BBK32, DbpA is involved in transmission via the lymphatic system, indicating that distinct modalities may be operative in borrelial dissemination (23,32,33,36). It is probable that B. burgdorferi has adapted to multiple routes of dissemination, as quick systemic infection is an important function for a pathogen that travels from host to host by tick bite at random locations.…”
mentioning
confidence: 99%
See 2 more Smart Citations